Difusi Inovasi untuk Keberlanjutan Bisnis Ritel Kecil: Strategi Pemasaran Digital - Antonius Juniadhi Soekandar; Putri Pratiwi (Universitas Sains dan Teknologi Komputer, 2023)
Background Study: There are small business owners who have not been able to choose the right strategy to implement digital marketing to increase sales. Purpose: This study aims to examine the strategies used by small retail business owners in implementing digital marketing in increasing the level of sales in their business. Method: The method used in this study is a qualitative research with multiple case study models. Data collection through semi-structured interviews with 6 small retail business owners in Semarang City who have successfully implemented technological innovation with digital marketing strategies to increase their sales levels. Sources of data that support this research were obtained through reviewing business documents, social media websites and analysis. Concept: This study was built with reference to the conceptual framework of Rogers' Diffusion of Innovation theory. The data analysis studied in this study covers four digital marketing motives: social media platform and strategy, strategy and challenges, content strategy, and follow-up strategy. Findings/Results: The results of the analysis state that digital marketing strategy is very important in business continuity and the strategic method applied is very important. The findings in this study can be utilized by small retail business owners who want to increase sales, manage the application of digital marketing technology and the challenges that will be faced better. Small retail business owners can also choose the strategies identified in this research in implementing the right digital marketing strategy for their business.